Contribution of Earth and Space Science Online Course to Development of TPACK for Prospective Science Teachers in Primary Education - Rukmana, Diki; Handayani, Sri Lestari (Universitas Muhammadiyah Surakarta, 2020)
Purpose: Prospective teacher educations has the challenge of being able to equip teachers with the skills to manage classroom learning by utilizing various technological resources. One approach that can be taken is to design lectures who can contribute to the development of TPACK. This study examines the suitability of online learning practices in earth and space science courses for the development of TPACK prospective for prospective science teachers in primary education. Methodology: The survey research was conducted on 68 students who took Earth and Space Science courses online in the even semester of 2019/2020. Factor Analysis and Structural Equation Modelling (SEM) were conducted to analyse the validity of the instrument and testing of hypotheses. Results: The result of the factor analysis showed that the 27 instruments used had sufficient correlation to confirm the structure of each variable. SEM analysis results show that online learning that has been implemented has a positive and significant effect on the development of pre-service teacher TPACK. Applications/Originality/Value: These findings are a reference for those who intend to develop an online learning framework that can support the development of TPACK for prospective teachers.